THE AERODYNAMICS ANALYSIS OF AIRFOILS FOR HORIZONTAL AXIS WIND TURBINE BLADE USING COMPUTATIONAL FLUID DYNAMIC - Mokhetar, Abdulhafiz Younis; Yohana, Eflita; Suryo Utomo, MSK. Tony (ROTASI, 2014)
This paper included in designing and simulating for 2D. It may use two software's called Gambit and FLUENT to generate the data from the fluid flow cases. In this research select two models NACA airfoil NACA4412 and NACA4415. Chose NACA 4412 because lift coefficient is higher than NACA4415. In this study computational flow  over an airfoil at different angles of attack  (0º, 5º,10º,15º ,20º)  using  CFD (Computational fluid dynamics) simulation two dimensional airfoil NACA 4412 and NACA4415 CFD models are  presented using ANSYS-FLUENT software. For this model Using turbulent viscosity k-epsilon (standard wall function)  near  the  wall and wind velocity 5 m/s  Here, NACA 4412 airfoil  profile  is considered  for analysis of wind turbine  blade. Geometry of airfoil is created using GAMBIT 2.4.6 and CFD analysis is carried out using FLUENT 6.3.26 at various  angles  of  attack  from  0º  to  20º. Lift and Drag forces along with the angle of attack are the important parameters in a wind turbine system. The Lift and Drag forces are calculated at different sections for angle of attack from 0o to 20o for low Reynolds number. The analysis  showed that the angle of attack of 10o has high Lift/Drag ratio. The airfoil NACA 4412 is analyzed based on computational fluid dynamics to identify its suitability for its application and good agreement is made between the results